tDCS Over the Motor Cortex Shows Differential Effects on Action and Object Words in Associative Word Learning in Healthy Aging - Branscheidt, Meret; Hoppe, Julia; Freundlieb, Nils; Zwitserlood, Pienie; Liuzzi, Gianpiero (Frontiers in Aging Neuroscience, 2017)
Healthy aging is accompanied by a continuous decline in cognitive functions. For example, the ability to learn languages decreases with age, while the neurobiological underpinnings for the decline in learning abilities are not known exactly. Transcranial direct current stimulation (tDCS), in combination with appropriate experimental paradigms, is a well-established technique to investigate the mechanisms of learning. Based on previous results in young adults, we tested the suitability of an associative learning paradigm for the acquisition of action- and object-related words in a cohort of older participants. We applied tDCS to the motor cortex (MC) and hypothesized an involvement of the motor cortex in learning action-related words. To test this, a cohort of 18 healthy, older participants (mean age 71) engaged in a computer-assisted associative word-learning paradigm, while tDCS stimulation (anodal, cathodal, sham) was applied to the left MC. Participants’ task performance was quantified in a randomized, cross-over experimental design. Participants successfully learned novel words, correctly translating 39.22% of the words after one hour of training under sham stimulation. Task performance correlated with scores for declarative verbal learning and logical reasoning. Overall, tDCS did not influence associative word learning, but a specific influence was observed of cathodal tDCS on learning of action-related words during the NMDA-dependent stimulation period. Successful learning of a novel lexicon with associative learning in older participants can only be achieved when the learning procedure is changed in several aspects, relative to young subjects. Learning success showed large inter-individual variance which was dependent on non-linguistic as well as linguistic cognitive functions. Intriguingly, cathodal tDCS influenced the acquisition of action-related words in the NMDA-dependent stimulation period. However, the effect was not specific for the associative learning principle, suggesting more neurobiological fragility of learning in healthy aging compared with young persons.